The Persistent Effects of Monsoon Rainfall Shocks in India: A Nonlinear VAR Approach - Matthias Hertweck; Bjoern Brey (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We examine the effects of monsoon rainfall shocks on agricultural output, wages, and prices in India. The effects are highly asymmetric: agricultural output falls by 16% after a negative shock, but a positive shock has no significant effects. Although the drop in agricultural output is very short-lived, it elicits a persistent decline (increase) in wages (food prices). This indicates that famines are caused by a persistent disruption in food acquisition, rather than by a shortage in food supply.
Keywords: C22; E32; O13; Q11; 330